2 - L’organisation internationale de la Francophonie : Instrument de Developpement ou de Dependance - Clement Stephane Dali, (African Sociological Review, 2019)
Questioning the embedding of the International Organization of the Francophonie in the global hegemonic order, the article undertakes a discourse analysis of the organization in both a Foucaldian and diachronic approach and a comparative and synchronic approach. Indeed, taking the institutions’ discourses seriously, especially in the postcolonial framework, is a good heuristic way to go beyond - and not necessarily to contradict - the spontaneous sociology secreted by militant action. We thus establish a flagrant contradiction between two types of discourse, on the one hand that produced by the Organization of the Francophonie on the Francophonie and on the other hand that produced by the French State on the Francophonie. When the first is envisaged on the mode of living together, the second has for matrix a will to dominate whose origin is of colonial essence. The article thus contributes to fueling reflections on the recasting and renewal of postcolonial relations by questioning the relevance of the ex- colonizeds’ commitment to power systems that favor their subjugation.